Partitioning of Ti, Al, P, and Cr between olivine and a tholeiitic basaltic melt: Insights on olivine zoning patterns and cation substitution reactions under variable cooling rate conditions - Lang, Sarah; Mollo, Silvio; France, Lydéric; Misiti, Valeria; Nazzari, Manuela (Chemical geology, 2022)
The mechanism governing the kinetic growth of olivine in dynamic volcanic settings has been the subject of considerable attention in recent years. Under variable cooling rate (CR) and undercooling (−ΔT) regimes, the textual maturation of olivine proceeds from skeletal/dendritic crystals to polyhedral morphologies by infilling of the crystal framework. Owing to the establishment of a diffusion-controlled growth regime, a sharp diffusive boundary layer develops in the melt next to the advancing olivine surface. In this context, we have quantified the apparent partitioning of Ti, Al, P, and Cr between olivine and a Hawaiian tholeiitic basaltic melt at P = 1 atm, fO2 = QFM-2 buffer, and CR = 4, 20, and 60 °C/h over a constant -ΔT = 85 °C. Differences in charge and/or size between the substituent minor cations and the major species in the olivine crystallographic site dominate the energetics of homovalent and heterovalent cation substitutions. While the entry of Ti in the olivine lattice site accounts for the simple exchange [TSi4+] ↔ [TTi4+], more complex charge-balancing coupled-substitution mechanisms have been determined for the incorporation of Al, P, and Cr, i.e., [MMg2+, TSi4+] ↔ [MAl3+, TAl3+], [2 TSi4+] ↔ [TP5+, TAl3+], and [MMg2+, TSi4+] ↔ [MCr3+, TAl3+], respectively. In order to maintain charge balance, the disequilibrium uptake of minor cations in rapidly growing crystals is controlled by the same substitution mechanisms observed under equilibrium crystallization. This finding is consistent with the achievement of a local interface equilibrium at the olivine-melt interface independently of the diffusive boundary in the melt. A statistical approach based on multivariate analysis of olivine/melt compositional parameters confirms that the control of melt structure on the partitioning of Ti, Al, P, and Cr is almost entirely embodied in the olivine structure and chemistry via charge compensation reactions. Therefore, the magnitude of minor element partition coefficients is weakly dependent on diffusion kinetics in the melt but rather strongly governed by olivine zoning patterns resulting from fast crystal growth rates. •Ti, Al, P, and Cr partitioning is investigated during olivine rapid growth.•Complex zoning patterns in olivine are characterized by variable cation enrichments.•Kinetic partitioning is governed by homovalent and heterovalent cation substitutions.•Ti substitutes for Si in the tetrahedral site of olivine.•Charge-balancing coupled-substitutions determine the incorporation of Al, P, and Cr.